Pathways and Microbiology of Thiosulfate Transformations and Sulfate Reduction in a Marine Sediment (Kattegat, Denmark) - Jørgensen, Bo Barker (1991)
Reductive and oxidative pathways of the sulfur cycle were studied in a marine sediment by parallel radiotracer experiments with (35)SO(4)(2-), H(2)(35)S, and (35)S(2)O(3)(2-) injected into undisturbed sediment cores. The distributions of viable populations of sulfate- and thiosulfate-reducing bacteria and of thiosulfate-disproportionating bacteria were concurrently determined. Sulfate reduction occurred both in the reducing sediment layers and in oxidized and even oxic surface layers. The population density of sulfate-reducing bacteria was >10(6) cm(-3) in the oxic layer, high enough that it could possibly account for the measured rates of sulfate reduction. The bacterial numbers counted in the reducing sediment layers were 100-fold lower. The dominant sulfate reducers growing on acetate or H(2) were gas-vacuolated motile rods which were previously undescribed. The products of sulfide oxidation, which took place in both oxidized and reduced sediment layers, were 65 to 85% S(2)O(3)(2-) and 35 to 15% SO(4)(2-). Thiosulfate was concurrently oxidized to sulfate, reduced to sulfide, and disproportionated to sulfate and sulfide. There was a gradual shift from predominance of oxidation toward predominance of reduction with depth in the sediment. Disproportionation was the most important pathway overall. Thiosulfate disproportionation occurred only as cometabolism in the marine acetate-utilizing sulfate-reducing bacteria, which could not conserve energy for growth from this process alone. Oxidative and reductive cycling of sulfur thus occurred in all sediment layers with an intermediate “thiosulfate shunt” as an important mechanism regulating the electron flow.